Professional antigen presenting cells in human herpesvirus 8 infection - Knowlton, Emilee R.; Lepone, Lauren M.; Li, Jun; Rappocciolo, Giovanna; Jenkins, Frank J.; Rinaldo, Charles R. (Frontiers in Immunology, 2013)
Professional antigen presenting cells (APC), i.e., dendritic cells, monocytes/macrophages, and B lymphocytes, are critically important in the recognition of an invading pathogen and presentation of antigens to the T cell-mediated arm of immunity. Human herpesvirus 8 (HHV-8) is one of the few human viruses that primarily targets these APC for infection, altering their cytokine profiles, manipulating their surface expression of MHC molecules and altering their ability to activate HHV-8 specific T cells. This could be why T cell responses to HHV-8 antigens are not very robust. Of these APC, only B cells support complete, lytic HHV-8 infection. However, both complete and abortive virus replication cycles in APC could directly affect viral pathogenesis and progression to Kaposi’s sarcoma (KS) and HHV-8 associated B cell cancers. In this review, we discuss the effects of HHV-8 infection on professional APC and their relationship to the development of KS and B cell lymphomas.